Schöner wohnen und besser leben - Christian Reiss (Recherches Germaniques)
Hans Sedlmayr was an influential Austrian art historian in the 20th century. With his book Der Verlust der Mitte, he reached a broad audience beyond academia in post-war Germany. He was also active in the conservation of the historic center of Salzburg and argued for the intrinsic relation of this historic ensemble with the surrounding landscape. In my paper, I argue that concepts from the organicist biophilosophy of the Weimar Republic were of central importance for Sedlmayr. They did not only allow for a connection between aesthetics and the human world, but also helped him to connect to the fields of nature and landscape conservation.